Examining Sentence Constructions in Law of Attraction Affirmations from Language Perspective - Sausina, Cut Nina (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2024)
This research discusses the sentences used in affirmation when applying Law of Attraction (LoA). The aims of this research are to introduce the sentences used in applying LoA successfully, and contribute in science and language fields. There are three research questions offered in this research, first. how do language elements are used in applying LoA, second, how are the sentences arranged to direct positive vibes, and the last, what words should be chosen to attract positive vibes. The data are taken from several books used by LoA practioners. The conclusions are the language elements used in LoA: nouns, verbs, adjectives, adverbs, possessive adjectives, prepositions, determiners, conjunctions, or pronouns, the sentences are arranged to direct positive vibes by applying Losier (2007) tools, namely identify desires, give your desire attention, and allow it, chosen words to attract positive vibes commonly are attracting, getting, come, radiate, better, worthy, good, grateful, effortlessly, every way, love, joy, positivity, abundance, and prosperity. Keywords: Law of Attraction (LoA), positive vibes, goals, word choices